Prospective study of primary amenorrhoea and its management in a rural tertiary centre - A., Pavanaganga; Ivalla, Sai Prathyusha; R., Nagarathnamma; A., Sailakshmi M. P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Amenorrhoea (absence of menstruation) is a symptom of varied causes. It results from dysfunction of hypothalamic-pituitary ovarian axis, uterus and vagina. It is a major concern for pubertal girls and their family members. It has a major impact on the physical, mental, psychological and social life of the girl and her family. The objective of the present study was to evaluate the aetiology and management of primary amenorrhoea in young adolescent girls. Methods: It was a prospective study conducted for a period of 2 years from August 2016 to July 2018 at Rajarajeswari medical college and hospital. Patients presenting with history of amenorrhoea that is, absence of menses by the age of 13 years with no visible development of secondary sexual characteristics or by 15 years of age with the presence of normal secondary sexual characteristics were included in our study. Cases of secondary amenorrhoea were excluded. Detailed history, examination, investigations and management was documented and analysed. Results: A total of 25 patients of primary amenorrhea were studied during the study period. In our study outflow tract anomalies were the commonest cause of amenorrhoea accounting for 84%, of which imperforate hymen (32%) and Mayer Rokitansky Küster Hauser syndrome (MRKH) 36% were the two most common Mullerian anomaly causing primary amenorrhoea. Gonadal dysgenesis accounted for 12% of the cases. Amenorrhoea was the commonest complaint patients presented with accounting to 76%, followed by cyclical pain abdomen accounting for 16% of cases. Conclusions: Primary amenorrhoea is multifactorial and is of major concern among adolescent girls. Early diagnosis and intervention has an impact on the physical and psychological wellbeing of the girl.